2014
DOI: 10.1603/ec13531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pesticide Application on Arthropod Pests of Nursery-Grown Maples

Abstract: Insecticides used against potato leafhopper, Empoasca fabae (Harris) (Homoptera: Cicadellidae), have been reported to cause problems with maple spider mite, Oligonychus aceris (Shimer) (Acarina: Tetranychidae), on nursery-grown 'Red Sunset' red maple and 'Autumn Blaze' Freeman maple. To test this, we conducted two experiments on field-grown trees in nurseries. In the first, the effects of early-season pesticide applications were examined during 2009. The second experiment was conducted in 2010 to compare effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Insecticidal applications that are used to control key pests like flatheaded appletree borer sometimes increase secondary non-target pests through reductions in their natural enemies. Prado et al (2014) found early-season insecticides for potato leafhopper (especially the pyrethroid, bifenthrin), as well as maple cultivar, were factors in increased abundance of maple spider mites in maple production plots. Ambrosia beetles prefer to attack stressed maple trees.…”
Section: Introductionmentioning
confidence: 95%
“…Insecticidal applications that are used to control key pests like flatheaded appletree borer sometimes increase secondary non-target pests through reductions in their natural enemies. Prado et al (2014) found early-season insecticides for potato leafhopper (especially the pyrethroid, bifenthrin), as well as maple cultivar, were factors in increased abundance of maple spider mites in maple production plots. Ambrosia beetles prefer to attack stressed maple trees.…”
Section: Introductionmentioning
confidence: 95%